PENGARUH UPAH TERHADAP TINGKAT PRODUKTIVITAS KERJA KARYAWAN PADA PERUSAHAAN PT.PP. LONDON SUMATERA INDONESIA Tbk DI BULUKUMBA - Rusydi, Muhammad; Astrini, A (Jurnal Ekonomi Balance, 2014)
Effect of Wages on Employee Productivity Level At Company PT. PP. London Sumatera Indonesia Tbkdi Bulukumba, The research was done by using simple linear equation method with t test. This method is conducted to determine the effect of wages on the level of productivity employee work in the company of PT. PP London Sumatera Tbk in bulukumba. Data in the form of Journals and Data obtained in the form of writing in the form of general overview of the company, namely data collection through obsveration and direct interviews in the office of the company related to the issues to be in carefully. The results concluded that there is influence between wages on employee productivity employee productivity work at PT. PP London Sumatera Indonesia Tbk Bulukumba District Tamatto Village.